IT Management Framework: a Practical Approach with IT Flowin Nexus (Applied in RSIA Stella Maris) - Darwin; Binarwan Halim (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
This research proposes and analyzes a novel hybrid IT management framework, IT Flowin Nexus, designed to address persistent challenges in the dynamic healthcare sector, specifically human resource inconsistency and lack of operational discipline. The framework addresses the conceptual gap in existing hybrid models by synthesizing structural foundations from Software Engineering, behavioral discipline from Rockefeller Habits, and quality assurance from Quality Management Systems (QMS). Using a qualitative case study at RSIA Stella Maris conducted over 23 weeks, the study employed rigorous data collection through semi-structured interviews with six key informants, direct observation of communication rhythms, and systematic document analysis. The framework's effectiveness was measured using the Project Consistency Index (PCI), a weighted metric (40% SOP, 30% WCM, 30% Task) developed to quantify team discipline. The findings show an absolute increase of 27 PCI points, shifting performance from a baseline of 50 to 77, with significant stabilization observed after the ninth week. Triangulated evidence confirms that the framework effectively translated strategic vision into tangible actions, resulting in improved project completion rates and a marked stabilization of system reliability. This research provides a practical roadmap for healthcare organizations to bridge the gap between flexible management and rigid operational consistency.